Elucidating the Activation Mechanism of AMPK by Direct Pan-Activator PF-739 - Aledavood, Elnaz; Gheeraert, Aria; Forte, Alessia; Vuillon, Laurent; Rivalta, Ivan; Luque, F. Javier; Estarellas, Carolina (Frontiers in Molecular Biosciences, 2021)
Adenosine monophosphate-activated protein kinase (AMPK) is a key energy sensor regulating the cell metabolism in response to energy supply and demand. The evolutionary adaptation of AMPK to different tissues is accomplished through the expression of distinct isoforms that can form up to 12 heterotrimeric complexes, which exhibit notable differences in the sensitivity to direct activators. To comprehend the molecular factors of the activation mechanism of AMPK, we have assessed the changes in the structural and dynamical properties of b1- and b2-containing AMPK complexes formed upon binding to the pan-activator PF-739. The analysis revealed the molecular basis of the PF-739-mediated activation of AMPK and enabled us to identify distinctive features that may justify the slightly higher affinity towards the b1-isoform, such as the b1-Asn111 to b2-Asp111 substitution, which seems to be critical for modulating the dynamical sensitivity of b1- and b2 isoforms. The results are valuable in the design of selective activators to improve the tissue specificity of therapeutic treatment.